OLIY TA’LIM MUASSASALARIDA BIOKIMYO FANINI SUN’IY INTELLEKT VA 3D MODELLASH ASOSIDA O’QITISH METODIKASI - Ixtiyarova G.A, Eshchanova N.Z (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The article discusses the use of artificial intelligence in biochemistry in higher education institutions, which improves the quality of knowledge and expands educational opportunities in the context of digitalization.It is believed that through the use of artificial intelligence systems to optimize and personalize educational processes, students gain a deeper understanding of the currently developing educational system.